It happens when the stage sets collapse - Schroeder, Carole (Nursing philosophy, 2003)
Sally Gadow's tenure as professor of nursing at the University of Colorado Health Sciences Center during my doctoral studies radically changed my view on science, nursing, relationships, and most importantly, the world. In this paper, I use ideas stimulated by Gadow's classes to argue that recognizing ambiguity through an attitude of metaphysical revolt can free nurses to form relationships with patients who are complex subjects rather than objects to be treated. I will first discuss Camus’ ideas of absurdity from the Myth of Sisyphus, comparing the awake passions of Don Juan and the maniacal (and fatal) love of Romeo and Juliet (1955). Merleau-Ponty's (1962) work on the dialectic of human sexuality sheds light on the intrinsic bodily ambiguity of human existence as seen through sexual attraction. de Beauvoir (1948) further lends insight into ideas of ambiguity, relationship, and freedom. Finally, I will argue that recognition of the intrinsic ambiguity of existence coupled with an attitude of metaphysical revolt may free nurses and patients from external frameworks that limit experience, impose meaning, and in the process, sever human relationship.